Brent Geese in Essex, 1957-1958 - Burton, P J K (Wildfowl, 1959)
The method of estimation, using the numbers of first-winter birds in samples of 50, has been continued. A greater number of samples than in previous years have been obtained, and these came from several localities as follows: Foulness - 22 samples; Stansgate (S. Blackwater - 5 samples; Osea I. (N. Blackwater) - 4 samples; Holbrook Bay, Suffolk (Stour estuary) - 2 samples; Dengie - 1 sample; Total 34. The counts cover the period 9 November 1957 to 15 March 1958. The mean number of first-winter birds per sample of 50 for 1957-58 was 26.32, with a standard deviation of 5.53, and standard error of the mean 0.95. There were no significant differences between the counts for different areas, or on different dates. These figures indicate a proportion of first-winter birds in the population of about 53%. A few brood sizes only were counted, and do not give a significant figure for the winter.